The Effect of Long-term Biofeedback Therapy on Depression of Elderly Stroke Patients - Razieh Yousefian Molla; Tahereh Hajiahmad; Rouzbeh Kazemi (Function and Disability Journal)
Background and Objectives: Depression is a common problem after stroke, with a high prevalence. Multiple studies have suggested that biofeedback therapy can effectively treat depression without causing side effects. This research aims to investigate the long-term impact of biofeedback therapy on depression in stroke survivors. Methods: A quasi-experimental study was conducted with 40 stroke patients who were divided into a rehabilitation control group and a rehabilitation group that underwent long biofeedback electromyography exercises. All patients were assessed for their level of depression at the start of the study and again after two years of treatment, after completing occupational therapy sessions with and without biofeedback intervention. Statistical analysis was performed using paired t-tests and correlated t-tests with a significance level (P≤0.05). Results: In both control and intervention groups, no significant differences were observed in the level of depression between the pre-test and post-test stages. However, a crucial difference was observed between the intervention and control groups after using biofeedback. The average depression in patients who used long-term biofeedback decreased after two years compared to the control group (P≤0.05). Conclusion: Long-term utilization of biofeedback therapy impacts the depression levels of stroke patients. This method is highly recommended as a complementary approach to conventional rehabilitation.